Differential-diagnostic and therapeutic challenges in the management of ruptured corpus luteum cyst with undiagnosed intrauterine pregnancy in the early first trimester and ruptured ovarian pregnancy - Akihiro Takeda; Shiori Tsuge; Shohei Iyoshi (IMR Press, 2022)
Background: The similarities in clinical features between ruptured corpus luteum cyst (RCLC) with undiagnosed intrauterine pregnancy in the early first trimester (RCLC-P) and ruptured ovarian pregnancy are well established. However, the identification of differences between these two morbid conditions is important to determine the causes and manage the hemoperitoneum without devastation of pregnancy in RCLC-P. Furthermore, the pregnancy outcomes after laparoscopic surgery in women with RCLC-P are not recognized. Methods: Retrospective observational study of six women with RCLC-P and seven women with ruptured ovarian pregnancy. Results: All cases were referred under strong suspicion of ruptured ectopic pregnancy due to lower abdominal pain and positive urinary pregnancy test after spontaneous conception. The estimated median number of gestational weeks in RCLC-P (5 weeks) was significantly lower than that for ruptured ovarian pregnancy (7 weeks). At triage, the median serum levels of beta-human chorionic gonadotropin (β-hCG) were significantly lower in RCLC-P (592 IU/L) than ruptured ovarian pregnancy (3723 IU/L) (p = 0.01). In all six cases with RCLC-P, laparoscopic ovary-sparing surgery was performed. Among the four women who received postoperative supplementation of progesterone, uneventful vaginal delivery occurred at term in three cases. Conclusions: Early gestational age and lower serum β-hCG levels at triage, as well as non-declining levels of serum β-hCG on the day after surgery, were significant predictors of RCLC-P rather than ruptured ovarian pregnancy. Laparoscopic surgery was a feasible option for the management of RCLC-P with appropriate postoperative luteal support to achieve successful obstetric outcomes.